MODEL QUANTUM TEACHING PADA PEMBELAJARAN PENJUMLAHAN DAN PENGURANGAN BILANGAN DI KELAS 2 SEKOLAH DASAR MELALUI TEKNIK PERMAINAN - - Dwiyono (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2009)
This research is the action research which the purpose is to know the increasing of under¬standing of the students in learning addition and substraction of number by using playing techniques. The learning with playing technique was implemented in the second grade of the elementary school of Landungsari 1 which has 29 students. In order to make the students happy to learn, motivated, and enthusias¬tic, in this research had been presented the Quantum Teaching Model. The procedure in this research is done in three steps, that is (1) plan of the research, (2) the procedure of action, and (3) the implementation of action. The result of the research are (1) the students always happy in learning, (2) the ability of the students in understanding place of value concept is better, (3) the ability and the capability of the stu¬dents in adding and subtracting two numbers become reach, because in the learning use manipulative material, (4) the average of the class in the end of learning is still lower, that is 67.3, but the ability of af¬fective and psychomotor of the students have better.